UNFOLDING STUDENTS’ COGNITION AND META-COGNITION SKILLS IN MATHEMATICS PROBLEM SOLVING - Himang, Celbert M; Novabos, Rosemarie O (Journal of Agriculture and Technology Management, 2015)
The goal of education is to help students acquire knowledge and develop skills which are compatible with their understanding and problem-solving capabilities at different ages. The study was conducted to examine the level of grade 7 high school students’ cognitive and metacognitive awareness in mathematics problem solving using Piagetian Paper Pencil Test of Bakken and the revised scoring procedure of Bird and Meta-cognitive Awareness Inventory of Schraw and Dennison. Data were gathered from 323 participants. Results showed majority (56.04%) of the students were in pre-operational level and only few (4.95%) were in formal operational level. Moreover, students were found out to be high in both the two components of meta-cognition as knowledge of cognition and regulation of cognition. Likewise, only on subcomponent of metacognitive awareness planning was found to have a statistical significance on predicting students’ mathematics problem solving performance. However, the high meta-cognitive awareness level on procedural knowledge, information management strategies and debugging strategies have practical impression on students’ performance in mathematics problem solving.